Youth participation in policy-making processes in the United Kingdom: a scoping review of the literature. Issue 2 (3rd April 2022) - Macauley, T; Rolker, H.B.; Scherer, M; Brock, J; Savona, N; Helleve, A; Knai, C
ABSTRACT: Young people's voices remain underrepresented in health policy processes. This scoping review focuses on the United Kingdom (UK) and investigates how and to what degree young people have participated in policy-making processes. We adapt an established framework categorizing how young people are involved in policy-related processes, ranging from advisory roles to communicating findings. We report a spectrum of practical examples, highlighting opportunities for successful policymaking with youth, in relation to key factors, such as type of involvement, role of facilitators, and the integration of young people in different stages of the process.